The emergence of the community brass band a study on band management of Banda Dos Bata Incorporation, Taytay, Rizal in the context of community organization - Caliwara, Benedict Martin F. (2014.)
This paper primarily intends to inspect and examine the system of band management of the Banda Dos Bata In., a local community brass band in Taytay, Rizal, which operates community services in the context of family-based tradition and community organization. This study thus seeks to undertand the band culture. The Band in Taytay, Rizal which is active in different seasonal and occasional events of the town.These civic affairs are locally-managed and supported by the community and agencies that have been important factors for integrated band management.
Thesis (B. Music) -- University of the Philippines, Diliman.